The Merdeka Curriculum and Local Wisdom: An Innovative Synergy in Shaping Student Character in South Sumatra, Indonesia - Zainuddin, Zainuddin (Journal of Cross-Disciplinary Sustainability Innovations, 2025)
Character education is a crucial aspect in shaping a generation with integrity amidst global challenges. The Merdeka Curriculum emerges as an educational innovation offering flexible learning approaches; however, the integration of local wisdom in strengthening student character remains underexplored systematically. This study aims to explore how local wisdom can be synergized in the implementation of the Merdeka Curriculum to enhance character education at the junior high school level. Using a descriptive qualitative approach, data were collected through observations, interviews with teachers, and document analysis in three junior high schools in Indonesia. The findings reveal that the incorporation of local values such as gotong royong (mutual cooperation), musyawarah (deliberation), and tolerance in both intraclass activities and the Pancasila Student Profile strengthening projects contributes to contextual character development among students. These results underscore the importance of culturally-based curriculum development as the foundation for character education. The implication is that schools need to design adaptive learning strategies aligned with local contexts to realize relevant and meaningful education.